Towards a Philosophy of Astrobiology - Aretxaga-Burgos, Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Based on the history of astrobiology and astrobiological literature, we explore the possibility and necessity of a Philosophy of Astrobiology, and propose a tentative definition of Philosophy of Astrobiology for being considered as a possible sub-discipline of Philosophy of Science, different from Philosophy of Biology. We include a Bibliography for a Philosophy of Astrobiology.